2016
DOI: 10.1038/srep39503
|View full text |Cite
|
Sign up to set email alerts
|

Periodic fluctuation of reference evapotranspiration during the past five decades: Does Evaporation Paradox really exist in China?

Abstract: Evidence that the pan evaporation or reference evapotranspiration (ET0) as the indicator of atmospheric evaporation capability have decreased along with the continuous increase in temperature over the past decades (coined as “evaporation paradox”) has been reported worldwide. Here, we provide a nationwide investigation of spatiotemporal change of ET0 using meteorological data from 602 stations with the updated data (1961–2011). In addition, we explore the trigger mechanism by quantitative assessment on the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
43
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 78 publications
4
43
4
Order By: Relevance
“…Exceeding the increasing trends in other part of northern hemisphere in the same latitude zones, the air temperature in TP has showed a warming of around 0.16 °C/decade since 1950s (Liu & Chen, ). Different from other regions with insignificant changing trends, the precipitation increased for most parts of the TP from 1960s (B. Wang, Bao, Hoskins, Wu, & Liu, ; Z. X. Xu, Gong, & Li, ), whereas the reference evapotranspiration in the TP based on updated data generally presents decadal variations rather than monotonic response to climate change reported in early studies (W. G. Wang, Shao, et al, ; W. G. Wang, Xing, et al, ; Xing et al, ). Meanwhile, frost and ice days in the eastern and central of the TP have significantly decreased from 1961 to 2005 (You, Kang, Aguilar, & Yan, ).…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…Exceeding the increasing trends in other part of northern hemisphere in the same latitude zones, the air temperature in TP has showed a warming of around 0.16 °C/decade since 1950s (Liu & Chen, ). Different from other regions with insignificant changing trends, the precipitation increased for most parts of the TP from 1960s (B. Wang, Bao, Hoskins, Wu, & Liu, ; Z. X. Xu, Gong, & Li, ), whereas the reference evapotranspiration in the TP based on updated data generally presents decadal variations rather than monotonic response to climate change reported in early studies (W. G. Wang, Shao, et al, ; W. G. Wang, Xing, et al, ; Xing et al, ). Meanwhile, frost and ice days in the eastern and central of the TP have significantly decreased from 1961 to 2005 (You, Kang, Aguilar, & Yan, ).…”
Section: Introductionmentioning
confidence: 75%
“…Wang, Bao, Hoskins, Wu, & Liu, 2008; Z. X. Xu, Gong, & Li, 2008), whereas the reference evapotranspiration in the TP based on updated data generally presents decadal variations rather than monotonic response to climate change reported in early studies (W. G. Xing et al, 2016). Meanwhile, frost and ice days in the eastern and central of the TP have significantly decreased from 1961 to 2005 (You, Kang, Aguilar, & Yan, 2008).…”
Section: Introductionmentioning
confidence: 88%
“…2002), who thought the reason was the sunlight decrease due to the increase in cloud coverage [11][12]. Stanhill et al (2001) also thought the reason was the sunlight decrease while due to the increase in aerosol concentration [32].…”
Section: Evaporation Paradox In Lijiang Watershedmentioning
confidence: 99%
“…The contrast between temperature increase and potential evapotranspiration decrease is called the "evaporation paradox" [11].…”
mentioning
confidence: 99%
“…Liu & Zhang 14 indicated that in the driest Northwest region of China, ET 0 decreased from 1960 to 1993 at the rate of 2.34 mm/year and increased thereafter up to 2010 at the rate of 4.80 mm/year. Xing et al 15 reported decadal variations in the ET 0 . Gao et al 16 reported a decreasing trend in ET 0 at 46.7% of the weather station sites and an increasing trend in ET 0 at 53.3% of the sites for the period of 1960 to 2012 in the arid and semiarid area of the West Liao River basin of China.…”
Section: Song Et Almentioning
confidence: 99%